Genetic and Epigenetic Changes in Somatic Hybrid Introgression Lines Between Wheat and Tall Wheatgrass. Issue 4 (9th February 2015) - Liu, Shuwei; Li, Fei; Kong, Lina; Sun, Yang; Qin, Lumin; Chen, Suiyun; Cui, Haifeng; Huang, Yinghua; Xia, Guangmin
Abstract: Broad phenotypic variations were induced in derivatives of an asymmetric somatic hybridization of bread wheat ( Triticum aestivum ) and tall wheatgrass ( Thinopyrum ponticum Podp); however, how these variations occurred was unknown. We explored the nature of these variations by cytogenetic assays and DNA profiling techniques to characterize six genetically stable somatic introgression lines. Karyotyping results show the six lines similar to their wheat parent, but GISH analysis identified the presence of a number of short introgressed tall wheatgrass chromatin segments. DNA profiling revealed many genetic and epigenetic differences, including sequences deletions, altered regulation of gene expression, changed patterns of cytosine methylation, and the reactivation of retrotransposons. Phenotypic variations appear to result from altered repetitive sequences combined with the epigenetic regulation of gene expression and/or retrotransposon transposition. The extent of genetic and epigenetic variation due to the maintenance of parent wheat cells in tissue culture was assessed and shown to be considerably lower than had been induced in the introgression lines. Asymmetric somatic hybridization provides appropriate material to explore the nature of the genetic and epigenetic variations induced by genomic shock.